Improving Leaf GOGAT Activity After the Post-Silking Period Contributes to High Grain Yield with Reduced Nitrogen in N-Efficient Maize - Haoyu Li; Yanbing Wang; Jian Wang; Meng Zhang; Wenbo Liu; Xiangling Li; Xiaohu Lin (Agronomy)
Breeding and cultivating low-N-efficient maize varieties to obtain high yields with less N fertilizer is important for addressing food demands and environmental pollution. However, few studies have investigated the physiological characteristics of low-N-efficient maize varieties. Therefore, we performed an experiment over four years to test two maize varieties (low-N-efficient variety: JNK728, and high-N-efficient variety: XY335) and five N application rates (N120: 120 kg·ha−1, N180: 180 kg·ha−1, N240: 240 kg·ha−1, N300: 300 kg·ha−1, and N360: 360 kg·ha−1). The optimal N application rates for JNK728 and XY335 were N180 and N300, which obtained the highest yields (11,754 and 12,752 kg·ha−1, respectively), N uptake efficiencies (1.32 and 0.93 kg·kg−1), and N harvest index (67.94% and 61.98%), compared with other N application rates. The key period for plant N accumulation was the R1–R6 stage, which contributed 35.2–49.7% and 40.8–53.8% to plant N accumulation at the maturation stage in JNK728 and XY335, respectively. In addition, N accumulation in the grain accounted for more than half (51.8–63.2%) of the total N accumulation in plants, and the leaf N transport amount after the post-silking stage was the primary source of grain N accumulation in both JNK728 and XY335. We also explored the key enzymes and genes related to the N transport amount and efficiency in leaves in the two maize varieties, and found that GOGAT was the key enzyme and GOGAT2 was the key gene for JNK728, whereas the AS enzyme and AS1 and AS3 genes were most important for XY335. Therefore, we suggest that molecular breeding programs should focus on the GOGAT2 gene in low-N-efficient maize varieties, and cultivation techniques should aim to improve the GOGAT enzyme activity after the post-silking period to achieve high yields and N utilization efficiencies with less N fertilizer.